IJMA' ABOUT PRAYER WEARING MASK DURING THE COVID-19 PANDEMIC - Kohari, Khalis (Spektra: Jurnal Ilmu-ilmu Sosial, 2021)
This simple article aims to get to know more deeply about the ijma' prayer wearing a mask during the Covid-19 pandemic, covering the mouth is called talatsub, scholars agree that the law is forbidden by the Prophet so it is makruh to pray using a mask to cover your mouth is makruh but don't forget something that was previously makruh can turn into permissible when there is a need there is a need in the term ushul fiqh "the law that is makruh can be lost if there is a need and need in it." Looking at the current conditions, if we pray without wearing a mask, we may be exposed to the corona virus or we can transmit the virus to others. Therefore, in this article, we try to get to know more about ijma' or the law of praying wearing a mask during the Covid-19 pandemic.